Cloning, Characterization and Expression Regulation in Response to High-Temperature Stress of TRAF7 Gene in the Sea Cucumber Apostichopus japonicus - Yanfeng ZHAO; Meijie LIAO; Jianlong GE; Jinjin WANG; Yingeng WANG; Xiaojun RONG; Bin LI; Yanting TAN (Progress in Fishery Sciences)
As an intracellular protein, tumor necrosis factor receptor-associated factor 7 (TRAF7) is involved in signal transduction and regulates host stress defense. In a previous transcriptome sequencing analysis of the high-temperature-stressed sea cucumber body wall, TRAF7 was significantly differentially expressed between healthy sea cucumbers and ulcered skin in high-temperature-stressed sea cucumbers. However, the structure of the TRAF7 gene and its specific expression pattern under high-temperature stress have not been reported. In this study, based on the results of sea cucumber genome sequencing, the full-length sequence of sea cucumber TRAF7 (named AjTRAF7) cDNA was obtained using RACE technology. Its structural features and distribution in the genome were analyzed, and gene expression was examined in different tissues and under high-temperature stress. AjTRAF7 has a total length of 2, 576 bp, an ORF length of 1, 770 bp, a 5´UTR length of 345 bp, a 3´UTR length of 461 bp, and encodes 589 amino acids; the molecular weight of the predicted protein is 65.6 kDa, the theoretical isoelectric point (pI) is 7.52, the instability coefficient is 32.34, and the total average hydrophilicity is –0.150. The AjTRAF7 protein contains a RING finger structural domain, a coiled-coil structural domain, six WD40 repeats, and the N-terminus contains a helical region. The predicted protein contained 30.05% α-helices, 6.62% β-turns, 36.84% irregular coils, and 26.49% extended strands and was predicted as a cytoplasmic protein. It had 41, 20, and 3 serine, threonine, and tyrosine phosphorylation sites, respectively, and the N-terminus of the protein had 3 asparagine glycosylation sites. Aligned with the sea cucumber genome sequences, evm.model.chr8.1363 and evm.model.chr8.1742 served as two copies of the gene. Evm.model.chr8.1363 contained 18 exons and 15 introns, and evm.model.chr8.1742 contained 17 exons and 14 introns. The evolutionary tree was constructed with the amino acid sequence of TRAF7. The results showed that the sea cucumber, bat starfish (Patiria miniata), and purple globular sea urchin (Strongylocentrotus purpuratus) clustered into one branch, and the sea cucumber was more similar to the bat starfish and the purple globular sea urchin, at 40.58% and 38.37%, respectively. RT-qPCR showed that AjTRAF7 was expressed in all tested tissues of healthy sea cucumbers. Its expression was highest in female gonads, followed by coelomocytes; it decreased in respiratory trees, body walls, intestines, male gonads, and longitudinal muscles in that order, and the difference in expression among tissues was significant (P < 0.05). Under high-temperature stress, AjTRAF7 expression in body wall tissues increased during the first four d and decreased in the subsequent four d. The results indicated that AjTRAF7 might be involved in regulating expression in response to high-temperature stress in sea cucumbers, and the results provide a scientific basis for analyzing the molecular mechanism of high-temperature stress in sea cucumbers.